Finding the principal disjunctive normal form (PDNF) of a Boolean expression












0












$begingroup$


Find the principal disjunctive normal form (PDNF) of a Boolean expression
$$((pwedge q) rightarrow r)vee((pwedge q)rightarrow neg r).$$
I tried by expanding it but I am stuck with the expression
$(neg p vee neg q vee r) vee (neg p vee neg q vee neg r)$. I don't know how to convert them into min terms. Please help me.










share|cite|improve this question











$endgroup$








  • 2




    $begingroup$
    Your last expression can be written as $text{Something}lor (rlor neg r)$.
    $endgroup$
    – Git Gud
    Jan 3 '16 at 19:20










  • $begingroup$
    First you must see that either the equation is sum of products or not.As it has only disjunctions, so it is not possible to find DNF for this equation.
    $endgroup$
    – Muhammad Asif
    Dec 20 '16 at 21:05
















0












$begingroup$


Find the principal disjunctive normal form (PDNF) of a Boolean expression
$$((pwedge q) rightarrow r)vee((pwedge q)rightarrow neg r).$$
I tried by expanding it but I am stuck with the expression
$(neg p vee neg q vee r) vee (neg p vee neg q vee neg r)$. I don't know how to convert them into min terms. Please help me.










share|cite|improve this question











$endgroup$








  • 2




    $begingroup$
    Your last expression can be written as $text{Something}lor (rlor neg r)$.
    $endgroup$
    – Git Gud
    Jan 3 '16 at 19:20










  • $begingroup$
    First you must see that either the equation is sum of products or not.As it has only disjunctions, so it is not possible to find DNF for this equation.
    $endgroup$
    – Muhammad Asif
    Dec 20 '16 at 21:05














0












0








0





$begingroup$


Find the principal disjunctive normal form (PDNF) of a Boolean expression
$$((pwedge q) rightarrow r)vee((pwedge q)rightarrow neg r).$$
I tried by expanding it but I am stuck with the expression
$(neg p vee neg q vee r) vee (neg p vee neg q vee neg r)$. I don't know how to convert them into min terms. Please help me.










share|cite|improve this question











$endgroup$




Find the principal disjunctive normal form (PDNF) of a Boolean expression
$$((pwedge q) rightarrow r)vee((pwedge q)rightarrow neg r).$$
I tried by expanding it but I am stuck with the expression
$(neg p vee neg q vee r) vee (neg p vee neg q vee neg r)$. I don't know how to convert them into min terms. Please help me.







boolean-algebra






share|cite|improve this question















share|cite|improve this question













share|cite|improve this question




share|cite|improve this question








edited Jan 4 '16 at 12:09









Random Jack

2,1161519




2,1161519










asked Jan 3 '16 at 18:46









BalajiBalaji

70117




70117








  • 2




    $begingroup$
    Your last expression can be written as $text{Something}lor (rlor neg r)$.
    $endgroup$
    – Git Gud
    Jan 3 '16 at 19:20










  • $begingroup$
    First you must see that either the equation is sum of products or not.As it has only disjunctions, so it is not possible to find DNF for this equation.
    $endgroup$
    – Muhammad Asif
    Dec 20 '16 at 21:05














  • 2




    $begingroup$
    Your last expression can be written as $text{Something}lor (rlor neg r)$.
    $endgroup$
    – Git Gud
    Jan 3 '16 at 19:20










  • $begingroup$
    First you must see that either the equation is sum of products or not.As it has only disjunctions, so it is not possible to find DNF for this equation.
    $endgroup$
    – Muhammad Asif
    Dec 20 '16 at 21:05








2




2




$begingroup$
Your last expression can be written as $text{Something}lor (rlor neg r)$.
$endgroup$
– Git Gud
Jan 3 '16 at 19:20




$begingroup$
Your last expression can be written as $text{Something}lor (rlor neg r)$.
$endgroup$
– Git Gud
Jan 3 '16 at 19:20












$begingroup$
First you must see that either the equation is sum of products or not.As it has only disjunctions, so it is not possible to find DNF for this equation.
$endgroup$
– Muhammad Asif
Dec 20 '16 at 21:05




$begingroup$
First you must see that either the equation is sum of products or not.As it has only disjunctions, so it is not possible to find DNF for this equation.
$endgroup$
– Muhammad Asif
Dec 20 '16 at 21:05










2 Answers
2






active

oldest

votes


















1












$begingroup$

Expression mentioned is a Tautology.
$$((p.q) rightarrow r)+((p.q)rightarrow r')=((p'+q'+r)+(p'+q'+r'))=p'+q'+1 = 1$$
So PDNF corresponding to it is
$$(p'.q'.r')+(p'.q'.r)+(p'.q.r')+(p'.q.r)+(p.q'.r')+(p.q'.r)+(p.q.r')+(p.q.r)$$






share|cite|improve this answer









$endgroup$





















    -1












    $begingroup$

    The required normal form is ( if I am not wrong ):-



    (p^q^r)v(~p^q^r)v(~p^~q^r)v(p^q^~r)



    Once you get the form : (¬p∨¬q∨r)∨(¬p∨¬q∨¬r)

    Treat this as (¬p)∨(¬q)∨(r)∨(¬p)∨(¬q)∨(¬r)

    And convert the individual literals into minterms.



    To convert any variable P to a minterm ,just add : ^(Qv~Q)^(Rv~R) to P

    That is :P^(Qv~Q)^(Rv~R)
    And then use the distributive laws.






    share|cite|improve this answer











    $endgroup$













      Your Answer





      StackExchange.ifUsing("editor", function () {
      return StackExchange.using("mathjaxEditing", function () {
      StackExchange.MarkdownEditor.creationCallbacks.add(function (editor, postfix) {
      StackExchange.mathjaxEditing.prepareWmdForMathJax(editor, postfix, [["$", "$"], ["\\(","\\)"]]);
      });
      });
      }, "mathjax-editing");

      StackExchange.ready(function() {
      var channelOptions = {
      tags: "".split(" "),
      id: "69"
      };
      initTagRenderer("".split(" "), "".split(" "), channelOptions);

      StackExchange.using("externalEditor", function() {
      // Have to fire editor after snippets, if snippets enabled
      if (StackExchange.settings.snippets.snippetsEnabled) {
      StackExchange.using("snippets", function() {
      createEditor();
      });
      }
      else {
      createEditor();
      }
      });

      function createEditor() {
      StackExchange.prepareEditor({
      heartbeatType: 'answer',
      autoActivateHeartbeat: false,
      convertImagesToLinks: true,
      noModals: true,
      showLowRepImageUploadWarning: true,
      reputationToPostImages: 10,
      bindNavPrevention: true,
      postfix: "",
      imageUploader: {
      brandingHtml: "Powered by u003ca class="icon-imgur-white" href="https://imgur.com/"u003eu003c/au003e",
      contentPolicyHtml: "User contributions licensed under u003ca href="https://creativecommons.org/licenses/by-sa/3.0/"u003ecc by-sa 3.0 with attribution requiredu003c/au003e u003ca href="https://stackoverflow.com/legal/content-policy"u003e(content policy)u003c/au003e",
      allowUrls: true
      },
      noCode: true, onDemand: true,
      discardSelector: ".discard-answer"
      ,immediatelyShowMarkdownHelp:true
      });


      }
      });














      draft saved

      draft discarded


















      StackExchange.ready(
      function () {
      StackExchange.openid.initPostLogin('.new-post-login', 'https%3a%2f%2fmath.stackexchange.com%2fquestions%2f1598685%2ffinding-the-principal-disjunctive-normal-form-pdnf-of-a-boolean-expression%23new-answer', 'question_page');
      }
      );

      Post as a guest















      Required, but never shown

























      2 Answers
      2






      active

      oldest

      votes








      2 Answers
      2






      active

      oldest

      votes









      active

      oldest

      votes






      active

      oldest

      votes









      1












      $begingroup$

      Expression mentioned is a Tautology.
      $$((p.q) rightarrow r)+((p.q)rightarrow r')=((p'+q'+r)+(p'+q'+r'))=p'+q'+1 = 1$$
      So PDNF corresponding to it is
      $$(p'.q'.r')+(p'.q'.r)+(p'.q.r')+(p'.q.r)+(p.q'.r')+(p.q'.r)+(p.q.r')+(p.q.r)$$






      share|cite|improve this answer









      $endgroup$


















        1












        $begingroup$

        Expression mentioned is a Tautology.
        $$((p.q) rightarrow r)+((p.q)rightarrow r')=((p'+q'+r)+(p'+q'+r'))=p'+q'+1 = 1$$
        So PDNF corresponding to it is
        $$(p'.q'.r')+(p'.q'.r)+(p'.q.r')+(p'.q.r)+(p.q'.r')+(p.q'.r)+(p.q.r')+(p.q.r)$$






        share|cite|improve this answer









        $endgroup$
















          1












          1








          1





          $begingroup$

          Expression mentioned is a Tautology.
          $$((p.q) rightarrow r)+((p.q)rightarrow r')=((p'+q'+r)+(p'+q'+r'))=p'+q'+1 = 1$$
          So PDNF corresponding to it is
          $$(p'.q'.r')+(p'.q'.r)+(p'.q.r')+(p'.q.r)+(p.q'.r')+(p.q'.r)+(p.q.r')+(p.q.r)$$






          share|cite|improve this answer









          $endgroup$



          Expression mentioned is a Tautology.
          $$((p.q) rightarrow r)+((p.q)rightarrow r')=((p'+q'+r)+(p'+q'+r'))=p'+q'+1 = 1$$
          So PDNF corresponding to it is
          $$(p'.q'.r')+(p'.q'.r)+(p'.q.r')+(p'.q.r)+(p.q'.r')+(p.q'.r)+(p.q.r')+(p.q.r)$$







          share|cite|improve this answer












          share|cite|improve this answer



          share|cite|improve this answer










          answered Jan 9 '17 at 5:24









          PriyPriy

          111




          111























              -1












              $begingroup$

              The required normal form is ( if I am not wrong ):-



              (p^q^r)v(~p^q^r)v(~p^~q^r)v(p^q^~r)



              Once you get the form : (¬p∨¬q∨r)∨(¬p∨¬q∨¬r)

              Treat this as (¬p)∨(¬q)∨(r)∨(¬p)∨(¬q)∨(¬r)

              And convert the individual literals into minterms.



              To convert any variable P to a minterm ,just add : ^(Qv~Q)^(Rv~R) to P

              That is :P^(Qv~Q)^(Rv~R)
              And then use the distributive laws.






              share|cite|improve this answer











              $endgroup$


















                -1












                $begingroup$

                The required normal form is ( if I am not wrong ):-



                (p^q^r)v(~p^q^r)v(~p^~q^r)v(p^q^~r)



                Once you get the form : (¬p∨¬q∨r)∨(¬p∨¬q∨¬r)

                Treat this as (¬p)∨(¬q)∨(r)∨(¬p)∨(¬q)∨(¬r)

                And convert the individual literals into minterms.



                To convert any variable P to a minterm ,just add : ^(Qv~Q)^(Rv~R) to P

                That is :P^(Qv~Q)^(Rv~R)
                And then use the distributive laws.






                share|cite|improve this answer











                $endgroup$
















                  -1












                  -1








                  -1





                  $begingroup$

                  The required normal form is ( if I am not wrong ):-



                  (p^q^r)v(~p^q^r)v(~p^~q^r)v(p^q^~r)



                  Once you get the form : (¬p∨¬q∨r)∨(¬p∨¬q∨¬r)

                  Treat this as (¬p)∨(¬q)∨(r)∨(¬p)∨(¬q)∨(¬r)

                  And convert the individual literals into minterms.



                  To convert any variable P to a minterm ,just add : ^(Qv~Q)^(Rv~R) to P

                  That is :P^(Qv~Q)^(Rv~R)
                  And then use the distributive laws.






                  share|cite|improve this answer











                  $endgroup$



                  The required normal form is ( if I am not wrong ):-



                  (p^q^r)v(~p^q^r)v(~p^~q^r)v(p^q^~r)



                  Once you get the form : (¬p∨¬q∨r)∨(¬p∨¬q∨¬r)

                  Treat this as (¬p)∨(¬q)∨(r)∨(¬p)∨(¬q)∨(¬r)

                  And convert the individual literals into minterms.



                  To convert any variable P to a minterm ,just add : ^(Qv~Q)^(Rv~R) to P

                  That is :P^(Qv~Q)^(Rv~R)
                  And then use the distributive laws.







                  share|cite|improve this answer














                  share|cite|improve this answer



                  share|cite|improve this answer








                  edited Dec 30 '18 at 12:14

























                  answered Dec 30 '18 at 12:09









                  Amrutesh MishraAmrutesh Mishra

                  11




                  11






























                      draft saved

                      draft discarded




















































                      Thanks for contributing an answer to Mathematics Stack Exchange!


                      • Please be sure to answer the question. Provide details and share your research!

                      But avoid



                      • Asking for help, clarification, or responding to other answers.

                      • Making statements based on opinion; back them up with references or personal experience.


                      Use MathJax to format equations. MathJax reference.


                      To learn more, see our tips on writing great answers.




                      draft saved


                      draft discarded














                      StackExchange.ready(
                      function () {
                      StackExchange.openid.initPostLogin('.new-post-login', 'https%3a%2f%2fmath.stackexchange.com%2fquestions%2f1598685%2ffinding-the-principal-disjunctive-normal-form-pdnf-of-a-boolean-expression%23new-answer', 'question_page');
                      }
                      );

                      Post as a guest















                      Required, but never shown





















































                      Required, but never shown














                      Required, but never shown












                      Required, but never shown







                      Required, but never shown

































                      Required, but never shown














                      Required, but never shown












                      Required, but never shown







                      Required, but never shown







                      Popular posts from this blog

                      How do I know what Microsoft account the skydrive app is syncing to?

                      When does type information flow backwards in C++?

                      Grease: Live!